Dynamic strength training improves insulin sensitivity without altering plasma levels and gene expression of adipokines in subcutaneous adipose tissue in obese men - Klimcakova, E; Polak, J; Moro, C; Hejnova, J; Majercik, M; Viguerie, N; Berlan, M; Langin, D; Stich, V (The Journal of clinical endocrinology and metabolism, 2006)
CONTEXT: Obesity is characterized by a low-grade inflammatory state, which could play a role in insulin resistance. Dynamic strength training improves insulin sensitivity. OBJECTIVE: The objective of this study was to investigate, in obese subjects, whether the insulin sensitizing effect of dynamic strength training is associated with changes in plasma levels and gene expression of adipokines potentially involved in the development of insulin resistance. DESIGN: Twelve obese male subjects were investigated before and at the end of 3 months of dynamic strength training. Insulin sensitivity was evaluated using euglycemic-hyperinsulinemic clamp. Blood samples and needle biopsy samples of sc abdominal adipose tissue were obtained. The plasma levels and adipose tissue mRNA levels of adiponectin, leptin, IL-1beta, IL-6, and TNF-alpha were determined. RESULTS: The training induced an increase in the whole-body glucose disposal rate by 24% (P = 0.04). The body weight was not altered during the training. Plasma levels of leptin decreased during the training (16.6 +/- 6.3 vs. 13.1 +/- 5.7 ng/ml) by 21% (P < 0.02), whereas no change in plasma levels of other adipokines and C-reactive protein was observed. Gene expression of the investigated adipokines was not changed in sc adipose tissue during the training. CONCLUSIONS: In obese subjects, the dynamic strength training resulted in an improvement of whole-body insulin sensitivity. The increase in insulin sensitivity was not associated with training-induced modifications of plasma levels or adipose tissue gene expression of adipokines supposedly involved in the development of insulin resistance.
Keywords: Cytokines; adiponektin; Tumor Necrosis Factor-alpha; svalová síla; Leptin; cytokiny; Obesity; Adiponectin; lidé; podkožní tuk; cvičení; Subcutaneous Fat; Interleukin-6; Muscle Strength; leptin; TNF-alfa; Interleukin-1beta; obezita; Male; Insulin Resistance; interleukin-6; inzulinová rezistence; exprese genu; interleukin-1beta; lidé středního věku; mužské pohlaví; Exercise; Middle Aged; Gene Expression; Humans